Grammatical rhymes in Polish poetry: A quantitative analysis. - Opara, Karol R. (Digital Scholarship in the Humanities, 2015)
Analysis and interpretation of poetry is based on qualitative features of its text such as its semantics or means of expression as well as on general knowledge about the author and artistic period. Recent advances in automatic text processing allow for performing quantitative analysis of large sets of poetry. Their results may facilitate assessment of linguistic capabilities of its author or, in other words, his poetic mastery. This contribution presents a method of calculating the share of grammatical rhymes in Polish poetry. It is used to create a ranking of both historic and contemporary Polish poets. Comparative study and statistical analysis is developed using Pan Tadeusz by Adam Mickiewicz as a reference poem for Polish poetry. Assessment of technical mastery is one step towards the introduction of objective measures of poetic quality.